Eyewitness the Negro in American history - Katz, William Loren (Pitman Publishing Corporation, 1967)
Illuminates the contributions of African Americans in every period of our history: from the early explorers to today's champions of true equality and civil rights. Clear narratives of every period set the stage for eyewitness accounts drawn from letters, army records, travel accounts, magazines, and other authentic sources of the times.